Youth Unemployment, Ageing and Regional Welfare: The Regional Labour Market Policy Response to Ageing in Sweden - Rauhut, Daniel; Kahila, Petri (European Spatial Research and Policy, 2012)
The aim of this paper is to discuss the regional labour market policy response to demographic ageing in Sweden and its consequences on the labour supply of young adults. Regions with ageing problems already experience significant problems at the labour market. The overall conclusion is that labour market policies in Sweden addressing the consequences of ageing fail to include young adults and the policies do not address regional heterogeneity regarding e.g. ageing and youth unemployment.